Cost optimization of Colored Gypsum Composites - Yıldızel, Sadık Alper; Kaplan, Gökhan (Uluslararasi Muhendislik Arastirma ve Gelistirme Dergisi, 2019)
Gypsum composites as decorative and construction elements have been widely used for many building types due to their certain architectonic styles. Decorative gypsum composites are not very durable and stable when compared to the other composites; therefore, they need to be rehabilitated in short periods. To meet the increasing demand in the sustainability of these types of composite, many researches have been conducted for improving its properties with the minimum cost.  The aim of this study was to obtain the optimum cost of the colored gypsum composites with the improved mechanical properties. Glass fiber reinforced, silica and expanded perlite reinforced gypsum composites were colored with the addition of brown, yellow, black and red pigments. The mechanical properties such as compressive strength and freeze thaw (F-T) resistance of the mixes were also examined. A cost optimization analyze were performed based on the experimental test results. Results revealed that the usage and the cost of the color pigment added gypsum composites can be primarily optimized.
Keywords: Color pigments; gypsum composites; Color pigments; gypsum; gypsum composites; gypsum; 12. Responsible consumption